Impact of HIV prevention programs on drug users in Malaysia. - Kamarulzaman, Adeeba (Lippincott, Williams & Wilkins, 2009)
Faced with a rising HIV epidemic among injecting drug users, harm reduction policies and programs were introduced in Malaysia in 2005. The positive impact seen since the introduction of these programs comprise the inclusion of the health aspects of illicit drug use in the country's drug policies; better access to antiretroviral therapy for injecting drug users who are HIV infected; reduction in HIV-risk behavior; and greater social benefits, including increased employment. Despite these achievements, tension between law enforcement and public health persists, as harm reduction exists alongside an overall drug policy that is based on abstinence and zero tolerance. Unless there is harmonization of this policy, sustainability and scale-up of harm reduction programs will remain a challenge.